2010
DOI: 10.1242/dev.052647
|View full text |Cite
|
Sign up to set email alerts
|

The neural crest-enriched microRNA miR-452 regulates epithelial-mesenchymal signaling in the first pharyngeal arch

Abstract: SUMMARYNeural crest cells (NCCs) are a subset of multipotent, migratory stem cells that populate a large number of tissues during development and are important for craniofacial and cardiac morphogenesis. Although microRNAs (miRNAs) have emerged as important regulators of development and disease, little is known about their role in NCC development. Here, we show that loss of miRNA biogenesis by NCC-specific disruption of murine Dicer results in embryos lacking craniofacial cartilaginous structures, cardiac outf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 59 publications
(57 reference statements)
1
67
1
Order By: Relevance
“…Ablation of Dicer in the myocardium using Nkx2.5Cre (Stanley et al, 2002) causes DORV with VSD, accompanied by upregulation of Pitx2 and Sema3c in the myocardium (Saxena and Tabin, 2010). Deletion of Dicer in NCCs leads to abnormal pharyngeal arch arteries, VSD, DORV or PTA (Huang et al, 2010;Sheehy et al, 2010). Several miRNAs are known to regulate cardiac septation and valve development.…”
Section: Micrornasmentioning
confidence: 99%
“…Ablation of Dicer in the myocardium using Nkx2.5Cre (Stanley et al, 2002) causes DORV with VSD, accompanied by upregulation of Pitx2 and Sema3c in the myocardium (Saxena and Tabin, 2010). Deletion of Dicer in NCCs leads to abnormal pharyngeal arch arteries, VSD, DORV or PTA (Huang et al, 2010;Sheehy et al, 2010). Several miRNAs are known to regulate cardiac septation and valve development.…”
Section: Micrornasmentioning
confidence: 99%
“…Similarly, disruption of miRNA biogenesis in NC cells is essential for cranial and cardiac neural crest development, but also specifically affects the expression of Dlx2 in the mandibular component of the first pharyngeal arch (PA1; Sheehy et al, 2010). In the same study, NC cells miRNA profiling showed that miR-452 is one of the most enriched and sufficient to rescue proper expression of Dlx2 in PA1.…”
Section: Micrornasmentioning
confidence: 88%
“…Eberhardt et al (2008), demonstrated for the first time that miRNA, in particular miR-140, affects cranial NC cells dispersion and modulates palatogenesis. After this pioneer work, several groups have demonstrated that miRNA are central regulators of NC development (Amaral and Mattick, 2008;Eberhart et al, 2008;Cordes and Srivastava, 2009;Xin et al, 2009;Ivey and Srivastava, 2010;Subramanyam and Blelloch, 2011).…”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistency between mRNA and protein expression for Fn and Sox10 might be caused by posttranscriptional regulation. Sheehy et al (39) have shown that the neural crestenriched miRNA miR-452 regulates non-cell autonomous signaling involving Wnt5a, Shh, and Fgf8 that converge on Dlx2 regulation in PA1.These results suggest that posttranscriptional regulation by miRNAs is required for ENCC differentiation and ENS formation. This finding could explain the changes in Fn and Sox10 protein expression that are correlated with invariant mRNA expression in the aganglionic hindgut of HSCR and further suggests that the regulation of Fn and Sox10 was at the protein level.…”
Section: Proteomics Of the Hindgut In Human Hscrmentioning
confidence: 97%